Pengaruh Pemupukan dan Mikoriza terhadap Pertumbuhan Tanaman Karet Muda Pada Model Peremajaan Bertahap - Yulius Ferry; Rusli Rusli; Juniaty Towaha (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Gradual rejuvenation model is an option to increase the productivity of smallholder rubber plantation due to old and damaged plants. The limitation of this model is the high variation of the growth of young plant in the field. This study aimed to determine the effect of extra fertilization and mycorrhiza on the growth of young rubber plants in the gradual rejuvenation model. The research was located at Ramsay Village, Way Tuba District, with red-yellow podzolic soil types and climate type of B2 according to Oldemand, from 2012 to 2014, and arranged in split plot design. The plant age, P1 (3 years old); P2 (2 years old); and P3 (1 year old) was denoted as the main plot, whereas the subplot is fertilizer dosage, D1 (100% of recommended dosage); D2 (100% of recommended dosage + mycorrhiza; D3 (125% of recommended dosage); D4 (125% of recommended dosage + mycorrhiza). Fertilizer application was done twice a year, while mycorrhiza were given once a year toward the end of the rainy season. The plant material used was PB 260 clone, with a standard agricultural practices such as weeding and watering during the dry season. Variables measured were plant height and girth. The results showed that application of 25% extra from the recommended dosage + mycorrhiza was able to accelerate the growth of young rubber plants. Fertilizer dose of 125% from the recommendation + mycorrhiza applied on 2-year-old plants exhibited the same growth with 3-year-old plant that treated with recommended dosage. This result indicates that mycorrhiza works synergistically with inorganic fertilizer, which enhances the effectivity and efficiency of extra fertilization in gradually rejuvenation models.